The Price of the Current Civilisation - D. Sachs, Jeffrey; Ghazali, Musa; Moghavvemi, Sedigheh (Asian Journal of Business and Accounting, 2013)
This paper is an extract from the public lecture delivered by Professor Dr. Jeffrey D. Sachs, at the invitation of Genting Berhad, in the Lim Goh Tong Lecture Hall of the Faculty of Business and Accountancy, University of Malaya. The lecture was the second in its series delivered on 23 October 2012. The talk was a detailed examination of current problems in the world economy and provides pointers to sustainable development for the future. It begins with explaining four fundamental drivers to global change: ‘economic convergence’, ‘rapid technological transformation’, ‘inequality’, and ‘environmental crises’. The fact that the US Government is under the influence of powerful private business interests, makes it unable to address the stated drivers to the global change required. Europe also faces similar issues with the added weakness of adopting a single currency without institutional support. All the four fundamental drivers to global change constitute issues for every part of the world, including Asia which is at the moment experiencing rapid growth in economic development, at the expense of social and environmental needs. There is a need for high taxes, a comprehensive social welfare system, public funded healthcare and investment for the young. Governments should have a long term economic plan that focuses on achieving the right balance of economic prosperity, social inclusion, and environmental sustainability. Keywords: Civilisation, globalisation, sustainability